1999
DOI: 10.1123/jsr.8.3.209
|View full text |Cite
|
Sign up to set email alerts
|

EMG Comparison of Selected Ankle Rehabilitation Exercises

Abstract: Many types of rehabilitation exercises are used to reestablish lower extremity neuromuscular function and strength following ankle injuries. It has not been established which exercise induces the greatest leg muscle activity, which might allow patients to recover more quickly from their injuries. The purpose of this investigation was to establish which exercises induce the most muscle activity in the medial gastrocnemius (MG), peroneus longus (PL), and tibialis anterior (TA), as measured by integrated electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Previous studies indicated that the level of muscle activation of the ankle musculature during a single-leg stance exercise was greater when performed on balance boards than when performed on flat ground. 1,4 Similar to our results, Braun Ferreira et al 3 determined that there was no difference in muscle activation of the TA, tibialis posterior, FL, and gastrocnemius muscles during a single-leg stance performed on a trampoline versus a balance board. Conversely, Blackburn et al 1 reported a greater EMG signal amplitude for the FL, TA, soleus, and gastrocnemius muscles when performing a single-leg stance exercise on a rigid platform compared to soft surfaces.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies indicated that the level of muscle activation of the ankle musculature during a single-leg stance exercise was greater when performed on balance boards than when performed on flat ground. 1,4 Similar to our results, Braun Ferreira et al 3 determined that there was no difference in muscle activation of the TA, tibialis posterior, FL, and gastrocnemius muscles during a single-leg stance performed on a trampoline versus a balance board. Conversely, Blackburn et al 1 reported a greater EMG signal amplitude for the FL, TA, soleus, and gastrocnemius muscles when performing a single-leg stance exercise on a rigid platform compared to soft surfaces.…”
Section: Discussionsupporting
confidence: 79%
“…1,11,14 However, there is very little information in the literature to help clinicians stage the progression of a program based on the relative muscular demands required from various balance platforms and exercises. 1,4,17 It is our impression that most clinicians consider the performance of balance exercises on a balance platform with a compliant surface to be more difficult than performing the same exercise on a platform with a rigid surface. The aim of this study was to quantify and compare the level of activation of the fibularis longus (FL), tibialis anterior (TA), and medial gastrocnemius (mGC) muscles during the performance of 4 exercises on 2 types of balance platforms.…”
mentioning
confidence: 99%
“…One of the most effective exercises to elicit automatic muscular contractions of the leg is Step Jump Run the ''T-Band Kick''. Several studies have demonstrated reflexive activation of muscles in the stance leg while kicking an elastic band (Cordova et al, 1999;Hopkins et al, 1999;Schulthies et al, 1998) with the other leg. For example, when kicking forward with the left leg, the hamstrings on the stance leg are activated.…”
Section: Sensorimotor Training Progressionmentioning
confidence: 97%
“…Current knowledge on the influence of commonly used balance equipment on muscle activity levels is based on studies including predominantly healthy subjects (11)(12)(13)(14). Thus far, no studies have evaluated the effect of balance surface type on muscle activity levels in subjects with CAI.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, no studies have evaluated the effect of balance surface type on muscle activity levels in subjects with CAI. However, maximally stimulating muscle activity levels is expected to accelerate the rehabilitation process to pre-injury functional levels (12). In addition, most balance protocols use unstable devices without control over the direction in which the ankle is challenged.…”
Section: Introductionmentioning
confidence: 99%